Renal cancer seeding metastases following retroperitoneoscopic-assisted cryoablation: A case report - van de Kamp, Maaike W.; Kortekaas, Bettina; Lagerveld, Brunolf W. (Canadian Urological Association Journal, 2015)
Nephron-sparing laparoscopy is the standard surgical treatment for clinical T1a renal tumours. However, the laparoscopic technique brings in its specific oncological safety concerns. Seeding metastases are reported: peritoneal metastases, port-tract metastases, and (sub-) cutaneous metastases. The method of laparoscopic assisted renal mass cryoablation is marked by the fact that traumatic tumour tissue handling is unavoidable. This case report reviews the rare occasion of seeding metastases in the retroperitoneal space following laparoscopic cryoablation of a small renal mass. The primary tumour showed no focal recurrence as reported by histological examination. The combination of two events as harming the integrity of cancer tissue and gas-circulation leading to the development of metastases in the retroperitoneal cavity is discussed. The combination of iatrogenic harming cancer tissue integrity and CO2-circulation leads to metastases in the retroperitoneal cavity. Therefore, we recommend performing image-guided renal mass biopsies before considering cryoablative surgery.